Performance of Mircoalgae Spirulina platensis in Oxidation Ditch Algae Reactor to Remove Nitrate in Domestic Wastewater - Nadiya Kamilalita; Euis Nurul Hidayah; Yayok Surya Purnomo (Future Science)
The high nitrate content in domestic wastewater can cause problems for the environment. Improved quality of processed wastewater can use biological treatment with oxidation ditch combined with microalgae Spirulina platensis. The growth process of Spirulina platensis requires nutrients such as nitrates. In the study, variations in aeration conditions (continuous aeration and intermittent aeration) were conducted to create anoxic conditions in oxidation ditch algae reactors. Observations were made for 5 days with the aeration process using a brush aerator rotation speed of 60 rpm. The results showed that the microalgae Spirulina platensis has the potential to be effective in degrading nitrate concentrations in domestic wastewater. In addition, intermittent aeration has a significant effect on nitrate degradation in domestic wastewater. This is indicated by a decrease in nitrate with a percentage removal of 73.71% from the initial nitrate concentration of 5.82 mg/l to 1.53 mg/l during intermittent aeration.